2010
DOI: 10.1111/j.1365-2745.2010.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Leftovers in seed dispersal: ecological implications of partial seed consumption for oak regeneration

Abstract: Summary1. Successful seed dispersal by animals is assumed to occur when undamaged seeds arrive at a favourable microsite. Most seed removal and dispersal studies consider only two possible seed fates, predation or escape intact. Whether partial consumption of seeds has ecological implications for natural regeneration is unclear. We studied partial consumption of seeds in a rodent-dispersed oak species. 2. Fifteen percent of dispersed acorns were found partially eaten in a field experiment. Most damage affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
119
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 35 publications
1
119
3
Order By: Relevance
“…Rodents and magpies are both predators and dispersers of acorns (Waite 1985), but rabbits and hares, which are abundant in our field site, are only predators (Zamora et al 1985;Díaz et al 1996;Leiva and Fernández 2003;Guzmán et al 2008). We have clear evidence of acorn predation in situ for a small fraction of the unprotected acorns but suspect that most of the unfound acorns were either entirely consumed immediately after removal or re-cached and consumed later in other sites (Perea et al 2011), as the farmland environment where our woodland islets are embedded may exacerbate predation. For instance, found in the Sierra Nevada Mountains (SE Spain) that most caches were recovered and consumed, and only 1.3 % of the original experimental acorns were found alive in caches the following spring.…”
mentioning
confidence: 99%
“…Rodents and magpies are both predators and dispersers of acorns (Waite 1985), but rabbits and hares, which are abundant in our field site, are only predators (Zamora et al 1985;Díaz et al 1996;Leiva and Fernández 2003;Guzmán et al 2008). We have clear evidence of acorn predation in situ for a small fraction of the unprotected acorns but suspect that most of the unfound acorns were either entirely consumed immediately after removal or re-cached and consumed later in other sites (Perea et al 2011), as the farmland environment where our woodland islets are embedded may exacerbate predation. For instance, found in the Sierra Nevada Mountains (SE Spain) that most caches were recovered and consumed, and only 1.3 % of the original experimental acorns were found alive in caches the following spring.…”
mentioning
confidence: 99%
“…Seed predation by predators cause severe loss of seed crops (Kurkjian ., 2016), but it has been proved that seed predators act as keystone species in some habitats (Brown and Heske, 1990). Seed predators contribute to seed germination by manipulating seeds (e.g., removing pericarp and seed coats), which may enhance germination if the prepared seeds are only partially, and not fully predated, or are dispersed far away or buried (Perea ., 2011;Yang and Yi, 2012). Seed dispersal is another important factor for the life cycles of most plants, as dispersal process includes 'departure of a diaspore (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Seedling establishment is also significantly affected by heavy partial consumption by rodents (Perea ., 2011). A few studies have observed that partially consumed acorns ( spp.)…”
mentioning
confidence: 99%
See 2 more Smart Citations